Effects of leaf beetle herbivory on pollination success and fruit development in woodland strawberry Fragaria vesca - Malm, Lisa (SLU/Dept. of Ecology, 2013)
Cultivating well-developed and marketable garden strawberries (Fragria x ananassa) and woodland strawberries (Fragaria vesca) depends on successful pollination by insects. Organic garden strawberry plantations harbour higher pollinator densities and have been shown to produce bigger and better developed fruits than conventional farms. However, organic cultivators sometimes face severe problems from herbivory by leaf beetles that forage on both leaves and flowers. This study aims to investigate how the damage on woodland strawberry by leaf beetle herbivores (Galerucella tenella and G. sagittariae) affect 1) the pollinators’ response to damaged vs. undamaged flowers, 2) pollination success, fruit weight and fruit development and 3) the production of flowers and runners. Two different plant types of woodland strawberry were used; the commercial variety Rügen were herbivore damage was focused on the flowers and wild genotypes that received herbivory on both leaves and flowers. Pollinators (bees and hover flies) clearly preferred undamaged flowers and there was no significant difference between pollinator groups. Both plant types had a higher pollination success in undamaged flowers compared to damaged ones but it was only significant in the Rügen plants. Rügen plants produced lighter fruits after florivory but there was no obvious effect on fruit weight after herbivory and florivory in the wild genotypes. There were less deformations from undamaged control flowers in Rügen plants but none of the plant types showed any significant effects of herbivory on the number of deformations. Hand pollination was done on at least one flower of each plant in both plant types to control that damage by herbivores caused lower pollination rather than direct damages that caused a lower weight or more deformations. Hand pollination caused an increase in weight for Rügen plants and decrease of deformations for both plant types, suggesting that pollen was limited. The number of runners produced during the experiment decreased with herbivory-damage while the number of produced flowers was unaffected by damage. To establish a more reliable way to cultivate woodland strawberries without pesticides it could be advantageous to further investigate the plants’ inherent defence to herbivores. There are also possibilities to decrease the amount of leaf beetles in cultivations through the hymenopteran parasitoid Asecodes lucens that should be further investigated.